2011
DOI: 10.3109/08958378.2011.622316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on pulmonary responses to acute ozone exposure in mice: role of TNFR1

Abstract: Context Chamber studies in adult humans indicate reduced responses to acute ozone with increasing age. Age-related changes in TNFα have been observed. TNFα induced inflammation is predominantly mediated through TNFR1. Objective To examine the impact of aging on inflammatory responses to acute ozone exposure in mice and determine the role of TNFR1 in age-related differences. Materials and methods Wildtype and TNFR1 deficient (TNFR1−/−) mice aged 7 or 39 weeks were exposed to ozone (2 ppm for 3 h). Four hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…Several investigators [27]–[30] have examined the effects of ozone, another powerful oxidant, in mice and rats and found that older animals showed either lesser functional decrements and lesser inflammatory responses compared to younger animals or no differences. Shore et al [27] found that levels of soluble TNF receptor 1 were increased in the older animals, and suggested that that this phenomenon might account for the decreased inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators [27]–[30] have examined the effects of ozone, another powerful oxidant, in mice and rats and found that older animals showed either lesser functional decrements and lesser inflammatory responses compared to younger animals or no differences. Shore et al [27] found that levels of soluble TNF receptor 1 were increased in the older animals, and suggested that that this phenomenon might account for the decreased inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…For RT-PCR, RNA was extracted from lungs and cDNA generated as previously described [42]. Endothelin 1, TrkB, fractalkine, and adipsin mRNA expression were quantified by real time PCR (7300 Real-Time PCR Systems, Applied Biosystems, US) using SYBR-green detection.…”
Section: Methodsmentioning
confidence: 99%
“…We used real-time PCR to quantitate IL-13 and IL-17A mRNA expression as described (Shore et al 2011). We subtracted Ct values for a housekeeping gene, 36B4 ( rplp0 ) (which codes for a ribosomal protein), from Ct values for IL-13 or IL-17A to obtain ΔCt values.…”
Section: Methodsmentioning
confidence: 99%